Genetic heterogeneity in rhabdomyosarcoma revealed by SNP array analysis. Issue 1 (20th October 2015) - Walther, Charles; Mayrhofer, Markus; Nilsson, Jenny; Hofvander, Jakob; Jonson, Tord; Mandahl, Nils; Øra, Ingrid; Gisselsson, David; Mertens, Fredrik
Abstract : Rhabdomyosarcoma (RMS) is the most common soft tissue sarcoma in children and adolescents. Alveolar (ARMS) and embryonal (ERMS) histologies predominate, but rare cases are classified as spindle cell/sclerosing (SRMS). For treatment stratification, RMS is further subclassified as fusion‐positive (FP‐RMS) or fusion‐negative (FN‐RMS), depending on whether a gene fusion involving PAX3 or PAX7 is present or not. We investigated 19 cases of pediatric RMS using high resolution single‐nucleotide polymorphism (SNP) array. FP‐ARMS displayed, on average, more structural rearrangements than ERMS; the single FN‐ARMS had a genomic profile similar to ERMS. Apart from previously known amplification (e.g., MYCN, CDK4, and MIR17HG ) and deletion (e.g., NF1, CDKN2A, and CDKN2B ) targets, amplification of ERBB2 and homozygous loss of ASCC3 or ODZ3 were seen. Combining SNP array with cytogenetic data revealed that most cases were polyploid, with at least one case having started as a near‐haploid tumor. Further bioinformatic analysis of the SNP array data disclosed genetic heterogeneity, in the form of subclonal chromosomal imbalances, in five tumors. The outcome was worse for patients with FP‐ARMS than ERMS or FN‐ARMS (6/8 vs. 1/9 dead of disease), and the only children with ERMS showing intratumor diversity or with MYOD1 mutation‐positive SRMS also died of disease. High resolution SNP array can be useful in evaluating genomic imbalances in pediatric RMS. © 2015 Wiley Periodicals, Inc.